2014
DOI: 10.1177/0022034514538973
|View full text |Cite
|
Sign up to set email alerts
|

Association of Carotid Intima–media Thickness and Atherosclerotic Plaque with Periodontal Status

Abstract: Studies have suggested an association between clinical/subclinical atherosclerosis and periodontal status. The purpose of this study was to investigate the association among maximal carotid intima–media thickness (cIMT), atherosclerotic plaque, and periodontal status in Chinese elderly patients. A cross-sectional study was conducted of 847 participants (age, 70.64 ± 9.03 yr) with ≥10 teeth. A questionnaire survey, routine biochemical tests, a periodontal examination, and maximal cIMT measurement were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
(44 reference statements)
1
26
0
1
Order By: Relevance
“…We did not find an association of PD with carotid IMT, consistent with a recent study in an Australian population with a median age of 39 years, and studies in China and Korea in older adults, all of which failed to show an association between mean PD or % PD ≥ 4 and carotid IMT (Jung et al 2014, Kapellas et al 2014, Yu et al 2014. The Japanese study was the one single study that reported a dose-response relationship between mean PD and carotid IMT (Hayashida et al 2013).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We did not find an association of PD with carotid IMT, consistent with a recent study in an Australian population with a median age of 39 years, and studies in China and Korea in older adults, all of which failed to show an association between mean PD or % PD ≥ 4 and carotid IMT (Jung et al 2014, Kapellas et al 2014, Yu et al 2014. The Japanese study was the one single study that reported a dose-response relationship between mean PD and carotid IMT (Hayashida et al 2013).…”
Section: Discussionsupporting
confidence: 88%
“…, Yu et al. ). To date, all these studies have been conducted in middle‐aged to elderly population (mean age > 60 years) with a higher BMI (mean 23–29 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Education level of the participants was classified as low (middle school or below, <9 years of education), middle (high school, >9 ≤ 12 years), and high (>12 years). Family income was classified as low (≤USD 120.85 per month), average (>USD 120.86 per month but ≤USD 362.54 per month), or high (≥USD 362.55 per month) (Yu et al , ). Participants were classified as smokers/drinkers (ever smoked/drank alcohol, including those who had quit) or never smokers/drinkers, married or divorced/single, and exercising regularly or not.…”
Section: Methodsmentioning
confidence: 99%